Insecticidal effect of Cryptocarya alba essential oil on the housefly, Musca domestica L. - Di Cosmo, Dania (2015)
The composition of the essential oil (EO) from Cryptocarya alba obtained by hydro distillation of fresh leaves was analyzed using gas chromatography (GC) and gas chromatography/mass spectrosmetry (GC/MS). The insecticidal effect of the oil on the house fly Musca domestica was evaluated by placing flies in a sealed glass jar containing a piece of EO-treated cotton yarn. The dose necessary to kill 50% of flies (LC50) in 0.5 and 1 h was determined at 26 ± 1 °C. The essential oil from Cryptocarya alba showed significant insecticidal properties [33.56 (7.06-159.50) mg/dm3 (0.5 h) and 15.07 (5.29-42.91) mg/dm3 (1 h)]. According to GC and GC/MS analysis a total of 38 compounds were identified. The composition of the Cryptocarya alba essential oil reported in this study is different to that reported in other publications with 4-terpineol (17.48%) ; 4- (3,3-dimethyl-but-1-ynyl) -4-hydroxy-2,6,6-trimethylcyclohex-2-enone (12.84%); 1,8-cineole (7.90%); p-cymene (7.11%) and sabinene (6.80%), accounting for 52.13% of the EO. The EO from Cryptocarya alba appears promising as a natural insecticide against houseflies. Keywords: Musca domestica; Cryptocarya alba; essential oil composition; GC-MS; NMR; natural insecticide.